Effects of Indwelling Pleural Catheter on Severe Acute Pancreatitis: A Retrospective Study - Qian Yao; Siyang Peng; Yanping Wu; Pi Liu (Gastroenterology Research and Practice)
Background. Pleural effusion (PE) is an important predictor for severity and prognosis of severe acute pancreatitis (SAP). However, there are few studies focused on the effects and timing of indwelling pleural catheter (IPC) on SAP. Considering this, we designed a retrospective study to verify the relationship between PE and severity of SAP and observe the effects and timing of IPC in SAP. Methods. A total of 309 SAP patients were enrolled. Based on the presence or absence of PE and IPC and IPC time, the enrolled patients were divided into 6 groups. Then, baseline parameters, disease severity, critical complications, ventilator supporting time (VST), length of stay (LOS), and 60-day mortality were compared between each two groups. Results. PE was a risk factor for death of SAP, but not an independent risk factor. SAP patients with PE rather without PE had higher critical complication rates (p<0.001), along with longer VST (p<0.001) and LOS (p<0.001). And the critical complication rates were lower in group 1 (IPC within 1 week of onset) than group 2 (IPC after 1 week of onset). Further, patients in group 1 also had shorter LOS (p=0.042) and VST (p=0.001) than those in group 2. In addition, the survival analysis showed the risk of death in the PE group was higher than the non-PE group (HR 6.6, 95% CI, 3.67–11.86, and p<0.001). And the risk of death in group 1 was lower than group 2 (HR 0.26, 95% CI, 0.08–0.84, and p=0.025). Conclusions. PE is a risk factor for death of SAP, but not an independent risk factor. IPC, especially IPC within 1 week of onset, has clinical practical value in SAP.